2002
DOI: 10.1093/annhyg/mef021
|View full text |Cite
|
Sign up to set email alerts
|

From Quartz Hazard to Quartz Risk: the Coal Mines Revisited

Abstract: Following the classification of quartz as a human carcinogen by the IARC, many standard-setting committees are currently trying to convert this hazard into their national or EU standards. Since human data to set a safe exposure limit for quartz are limited, we hypothesized that lung burden data on quartz in coal miners' lungs after lifetime exposure could be used to set a non-carcinogenic lung burden of quartz, and that this might be valid for other groups occupationally exposed to quartz. A review of data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For example, the collagen fibers of the tissue increased significantly over time, indicating that the lung tissue fibrosis caused by the coal dust progressed slowly, in contrast to that caused by silica, asbestos, and bleomycin ( Cao et al, 2021 ; Watanabe et al, 2021 ). We take 16 mg coal dust to a mouse in a month, which is approximately a miner 10 to 20 years exposure ( Henneberger & Attfield, 1997 ; Borm & Tran, 2002 ). These suggested that the mouse model was constructed in accordance with the development of CWP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the collagen fibers of the tissue increased significantly over time, indicating that the lung tissue fibrosis caused by the coal dust progressed slowly, in contrast to that caused by silica, asbestos, and bleomycin ( Cao et al, 2021 ; Watanabe et al, 2021 ). We take 16 mg coal dust to a mouse in a month, which is approximately a miner 10 to 20 years exposure ( Henneberger & Attfield, 1997 ; Borm & Tran, 2002 ). These suggested that the mouse model was constructed in accordance with the development of CWP.…”
Section: Discussionmentioning
confidence: 99%
“…Borm et al. reported a no observed adverse effect level (NOAEL) for quartz of between 0.03 and 0.13 mg/m 3 (40 year exposure) 7 based on an autopsy study for humans showing that lung burdens between 0.7 and 1.7 g of quartz are associated with macules only and not simple coal worker’s pneumoconiosis 8 .…”
Section: Introductionmentioning
confidence: 99%